Biblioterapia, duración de estancia hospitalaria, y estado emocional en niños con patologías infecciosas en el Hospital General Isidro Ayora - Ramírez Piedra, Karina Lizbeth (2020)
Pediatric hospitalization is a challenging reality as it is a population that involves third parties due to their nature of dependence. Also, this age group has other exclusive characteristics that currently represent needs not yet resolved by a health system. Thus, causes a gap in the resolution capacity of the problems that the pediatric patient faces in hospitalization. With the present investigation, we sought to evaluate whether bibliotherapy can help the hospitalized child to build up their resilience, improving emotional state, and reducing the length of hospital stay. A research was carried out with 40 children admitted for infectious diseases at the Isidro Ayora General Hospital, between May and July 2019. We applied the ASQSE (Ages and Stages Questionnaire: Social-Emotional), and PANAS-N (Positive and Negative Affect Scale), by age. As a relevant result we found that: bibliotherapy using books and readers chosen by the patient, in short periods (10 to 20 min/day), generate significantly improvement in the positive affect of participants older than 6 years (p < 0.01). Conclusions: The hospitalization time in children with bibliotherapy intervention was two to seven days, with the highest number of discharges at three days. There was a great improvement in the emotional state in the bibliotherapy group, specifically of the positive affect in children aged six to thirteen. There is no significant relationship between hospitalization time and changes in emotional state. Keywords: Bibliotherapy, pediatric hospitalization, positive affect.